Close eye or closed eye: The case of export misinvoicing in Bangladesh - Gupta, Pranav Kumar; Roy, Devesh; Ahmad, Kaikaus (International Food Policy Research Institute, 2012)
Export subsidies can generate or curb many perverse incentives for exporters, their expansionary effects on exports notwithstanding. These include expansion into soft markets or even deflection of domestic production into markets with similar taste and product specifications. Also, if there is under-invoicing, in principle it should decline with export subsidies since the government makes cash transfers based on the invoice presented to the authorities. In this paper, we study the effect of export subsidies on the under-invoicing of exports in Bangladesh. In a framework that allows for unobserved heterogeneity among importing countries and product specificities, we find evidence for under-invoicing in Bangladesh. The evidence at first seems counterintuitive, with a statistically significant increase in under-invoicing after introduction of a subsidy. After a more careful analysis, however, the positive incentives for under-invoicing can be explained by reasons such as black market premium (BMP) in foreign exchange markets or domestic tax evasion (among other factors). Even though BMP has been declining in Bangladesh over time, the incentives to evade domestic taxes (particularly with a nonlinear tax schedule and inclusion of subsidies on the inflow side of a firm’s balance sheet) remain strong, bolstered by weak enforcement.